Wide field of view imaging of premotor and sensorimotor cortex activation patterns by functional near infrared spectroscopy - Chand, Pankaj (ProQuest Dissertations & Theses, 2010)
Functional near infrared spectroscopy (fNIRS) is a non-invasive optical technique which can measure concentration changes of oxygenated (HbO), deoxygenated (HbR), and total hemoglobin (HbT) in brain tissue that are induced by neuronal activation. A major hindrance at present for brain optical imaging research is the limited field of view (FOV) size, which is restricted due to the limited number of source-detector pairs that current fNIRS hardware technology and cost considerations allow. As a result it is challenging to simultaneously capture hemodynamic changes in the premotor, motor and sensory cortex as some of these activations can occur outside the available FOV. My research focuses on the design of a new probe holder assembly for the DYNOT (NIRx Inc.) fNIRS imaging system which enables larger FOV imaging that encompasses the premotor, motor and sensory cortex regions. The probe holder assembly consists of (a) a portable stand that supports the weight of optical fiber bundles up to a few centimeters above the head’s surface and (b) a pliable probe holder that guides the fiber bundles onto the head's surface and ensures good optical contact with the scalp. The pliable probe holder consists of a sandwich of several different layers of materials that were chosen to attain a reasonable compromise between the requirement for flexibility to fit well onto the scalp and for rigidity to hold stably the source-detector fiber bundles vertically onto the head’s surface. The portable stand significantly alleviates the problem of the DYNOT’s fiber bundles heavy weight that created comfort issues for the subjects being imaged. Therefore the maximum available number of source-detector pairs could be used, which enabled imaging over a larger FOV without affecting subject comfort. The probe holder fixed the placement of DYNOT’s bifurcated source-detector fiber bundles on a regular spacing arrangement that kept nearest neighbors at a distance of 2.2 cm and next-nearest neighbors at a distance of 3.2 cm. As a result, in the current study 32 source-detector pairs were used that covered 8.4 x 12 cm area spanning the premotor, motor and sensory cortex. Having established a larger FOV we evaluated how different hand and arm motions activated different premotor, motor and sensory areas. More specifically, we employed activations protocols entailing group finger tapping, sequential finger tapping, squeezing a soft ball and flipping cards form a deck. We also used a purely sensory stimulation protocol as a control. These protocols enabled us to study differences in timing and localization of activation in different cortical regions, as elicited from each task. We present results for each of these activation protocols for three subjects. In addition, we have also studied the resting state connectivity for seed locations corresponding to the maximum activation locations in premotor, motor and sensory cortical regions, as identified during performance of the activation protocols. We also present the use of a spatiotemporal clustering algorithm that was adapted from the functional Magnetic Resonance Imaging (fMRI) literature to assess the physical size of activation/deactivation regions for each of these protocols in a quantitative fashion. The results from this clustering analysis indicate that different cortical activation regions are physically adjacent, a fact that is not evident from visual inspection of the activation images. This work presents for the first time, to our knowledge, activation images over a FOV that is larger than was previously reported, thus enabling simultaneous observation of spatiotemporal activation patterns in different cortical regions during performance of activation protocols. Future developments such as the outfitting of the DYNOT source-detector fiber bundles with brush-like optical fibers will enable improved comfort and optical contact during measurements, which can be very helpful for other clinical uses.